METHODS OF GUESSING GAMES IN LEARNING ARABIC LANGUAGE TO IMPROVE MAHARAH KALAM STUDENTS IN MADRASAH - Aini, Nur; Fawaid, Achmad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to find out: 1) the charades game method in learning Arabic to improve students' Maharah Kalam at Madrasah Ibtidaiyah Nurul Mun'im, 2) to find out the supporting and inhibiting factors for the application of the charades game method in learning Arabic to improve maharah kalam nurul mun'im madrasah ibtidaiyah students. This study uses a qualitative case study approach. Which focuses on a natural approach to meaning in data derived from field events that seek to understand. To obtain the data, the researcher associated data collection methods in the form of interviews, observation and documentation